Structure of Microseisms from Bay of Bengal (MAUSAM, 1966)
The ground motion of microseisms from the Bay of Bengal was studied with the help of records obtained from the three component seismographs of the Press-Ewing type. The results of the study indicate that the microseisms from the Bay of Bengal consist of 70 per cent Rayleigh waves and 30 per cent Love waves.